Unsur Piil Pesenggiri Dalam Tradisi Ngelemang Pada Masyarakat Adat Lampung Barat - Muhtadin Muhtadin; Nesia Mu’asyara (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
Progress over time often becomes a problem for the existence of traditions and culture in various regions in Indonesia. Ngelemang is one of the local traditions in the Lampung area, which still exists despite the erosion of its existence due to the inevitable modern trend. This research aims to examine the elements and values of Piil Pesenggiri which researchers limit to the value of sakai sambayan in the ngelemang tradition in the Way Mengaku community, West Lampung. The method used is descriptive qualitative with a field research approach, through observation, interviews, and documentation and by supplementing with references from related journal articles. The results of the research show that although the ngelemang tradition is still carried out, there is a decline in community participation, especially the younger generation, due to changes in lifestyles that are more individualistic. However, the value of sakai sambayan is still strongly held because this tradition prioritizes togetherness and mutual respect in its implementation. The recommendation from this research is that more efforts are needed to strengthen the inheritance of traditions to the younger generation and increase community involvement in preserving this culture.